2014
DOI: 10.1002/ab.21531
|View full text |Cite
|
Sign up to set email alerts
|

Employing music exposure to reduce prejudice and discrimination

Abstract: Whereas previous research has mainly focused on negative effects of listening to music on intergroup attitudes and behavior, the present three experiments examined whether music exposure could reduce prejudice and discrimination. In fact, those participants who had listened to songs with pro-integration (relative to neutral) lyrics expressed less prejudice (Studies 1 and 3) and were less aggressive against (Study 2) and more helpful toward an outgroup member (Study 3). These effects were unaffected by song lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 60 publications
1
26
0
1
Order By: Relevance
“…Playing a prosocial video game for only 20 minutes prompted participants to be more helpful toward the partner by assigning them more easy puzzles. Similar short-term effects have been found for listening to music with prosocial lyrics (Greitemeyer, 2009a(Greitemeyer, , 2009bGreitemeyer & Schwab, 2014). In one study, 53% of participants were willing to donate money to a nonprofit organization after listening to songs with prosocial lyrics, compared to 31% among participants who listened to neutral songs (Greitemeyer, 2009a).…”
Section: Abstract: Prosocial Behavior Empathy Helping Prosocial Mementioning
confidence: 60%
“…Playing a prosocial video game for only 20 minutes prompted participants to be more helpful toward the partner by assigning them more easy puzzles. Similar short-term effects have been found for listening to music with prosocial lyrics (Greitemeyer, 2009a(Greitemeyer, , 2009bGreitemeyer & Schwab, 2014). In one study, 53% of participants were willing to donate money to a nonprofit organization after listening to songs with prosocial lyrics, compared to 31% among participants who listened to neutral songs (Greitemeyer, 2009a).…”
Section: Abstract: Prosocial Behavior Empathy Helping Prosocial Mementioning
confidence: 60%
“…Greitemeyer, Hollingdale and Traut-Mattausch (2015) showed that listeners' attitudes and behaviours towards women were positively enhanced after the reception of songs with lyrics that advocate gender equality. Other studies reported that listening to music with prosocial lyrics is associated with less prejudice and discrimination (Greitemeyer & Schwab, 2014), less risky driving behaviour (Greitemeyer, 2013) and less antisocial behaviour (Greitemeyer, 2011). Yu and colleagues (2019) showed that even song lyrics without accompanying music can enhance prosocial behaviour.…”
Section: Prosocial Lyricsmentioning
confidence: 99%
“…These findings come mostly from a series of experimental studies conducted by Greitemeyer (2009a, 2009b, 2013) and the field studies of Jacob, Guéguen, and Boulbry (2010) and Ruth (2017a). Other studies have shown that this kind of music can decrease antisocial behavior (Böhm, Ruth, & Schramm, 2016; Greitemeyer, 2011; Greitemeyer & Schwab, 2014). In a longitudinal study, Coyne and Padilla-Walker (2015) showed that the long-term effect of prosocial content is rather small compared with the effects of aggressive and sexual lyrics.…”
Section: Introductionmentioning
confidence: 99%